Different Concepts of Derivatives - Ojha, Bhuwan Prasad (Journal of Advanced College of Engineering and Management, 2018)
In this paper, different concept of derivatives with some properties has been introduced. In differential calculus, the partial derivative, directional derivative and total derivative are studied. Their generalization for Banach spaces are the Gateaux differential and Freshet derivative.Journal of Advanced College of Engineering and Management, Vol.3, 2017, Page: 11-14